Modified SPC for short run test and measurement process in multi-stations - Koh, C.K. (Institute of Physics Publishing, 2018)
Due to short production runs and measurement error inherent in electronic test and measurement (T and M) processes, continuous quality monitoring through real-time statistical process control (SPC) is challenging. Industry practice allows the installation of guard band using measurement uncertainty to reduce the width of acceptance limit, as an indirect way to compensate the measurement errors. This paper presents a new SPC model combining modified guard band and control charts (Z chart and W chart) for short runs in T and M process in multi-stations. The proposed model standardizes the observed value with measurement target (T) and rationed measurement uncertainty (U). S-factor (Sf) is introduced to the control limits to improve the sensitivity in detecting small shifts. The model was embedded in automated quality control system and verified with a case study in real industry. Â© Published under licence by IOP Publishing Ltd.